(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
The article provides a comprehensive scientific analysis of the concept of Universal Design as a fundamental tool for shaping a modern inclusive urban environment. Based on the study of Norway’s leading expertise, the mechanisms for transforming theoretical principles of architectural barrier-free design into practical spatial solutions are investigated. The author explores the essence of the seven fundamental principles of Universal Design, emphasizing aspects such as equitable use, flexibility, intuitiveness, and low physical effort. A number of landmark objects are examined, including the Oslo Opera House, Schandorff Square, and revitalized industrial complexes. These examples demonstrate the implementation of "seamless space," multimodal navigation, and cognitive accessibility. Particular attention is paid to the socio-economic efficiency of universal planning and its role in stimulating urban mobility. In the context of the current challenges facing Ukraine, the necessity of implementing Norwegian "Design for All" standards into post-war reconstruction strategies is justified. The author argues that Universal Design is not only a requirement for social justice but also an effective instrument for increasing the capitalization of the architectural environment and fostering a democratic society where every citizen is granted equal rights to a comfortable and safe life. For Ukraine, in the context of the global challenge of large-scale post-war reconstruction, Norway’s experience is of strategic significance. Today, Ukraine faces a unique opportunity to achieve a civilizational transition from outdated post-Soviet standards of ’nominal accessibility’ — which often existed only declaratively — to the creation of cities where every individual feels like a full participant in social life. The Norwegian path convincingly demonstrates that universal design is not a financial burden on a project, but rather serves as an effective tool for enhancing the quality and capitalization of the built environment. Integrating inclusive solutions directly into the ’genetic code’ of architectural projects is the most promising development vector for the recovery of Ukrainian cities, enabling the formation of an equitable, safe, and open society of the future.